The Effectiveness of Using Scan Cards in Improving the Early Reading Skills of 4-Year-Old Children: Keberkesanan Penggunaan Kad Imbasan dalam Meningkatkan Kemahiran Awal Bacaan Kanak-Kanak 4 Tahun - Henry, Jacintha; Mamat, Nordin bin (Jurnal Pendidikan Bitara UPSI, 2022)
This study aims to explore teacher best practices on learning through activities using scan cards in Taska. This study a conducted to improve child early reading skills by using scan cards among kindergarten pupils. The target group for the researcher’s action research this time is three three-year-old students from a nursery located in the Hulu Bernam district. The problem found in this class is that children do not understand the early concepts of reading and have difficulty identifying vowel letters as well-solving questions related to vowel letters. The objective of the study was to recognize vowel letters, sound out vowel letters using and interest children using scan cards. The study design was Action Research using qualitative methods. The method used was to use a scan card to complete the worksheet given by the researcher. Data collection for this stud was obtained through observations like worksheets, observation checklists, and photographs. For data analysis, researchers use WPS Office (Writer, Presentation, and Spreadsheets). The implementation of the study is through four phases of the study, namely planning, acting, implementing, and reflecting. Findings of the study have proven that (1) Practical activities using scan cards can improve children’s proficiency in pronouncing vowels, (2) Proficiency in pronouncing vowels well, and (3) The use of appropriate materials can improve children’s language proficiency. Reflections on research show that teaching through practical activities can attract students’ attention and arouse enthusiasm in children. In general, this study can facilitate the task of educators well as raise the spirits of students to engage in such activities.